Efficacy of Amistar in Controlling Alternaria Blight and Yield of Mustard Variety Rai-5 - Hossain, I; Akter, MA; Anwar, MB (Journal of Environmental Science and Natural Resources, 2019)
The effect of Amistar in controlling Alternaria blight of mustard was investigated and the selected mustard variety Rai- 5 was used. Amistar @ 0.05% (1 spray), 0.05% (2 spray), 0.05% (3 spray), 0.1% (1 spray), 0.1% (2 spray) and 0.1% (3 spray) were sprayed at 14 days interval beginning from 40 days after sowing (DAS). Amistar resulted significant reduction of the disease Alternaria blight (Alternaria brassicae and Alternaria brassicicola) severity and increased seed yield. Out of the doses of Amistar used, 0.1% (3 spray) showed marked effect in reducing the disease over control in terms of reduction of % Alternaria blight incidence, % leaf infection and % leaf area diseased up to 90.72%, 90.42% and 98.17%, respectively as well as reduction of % siliqua infection and % area of siliqua diseased up to 96.17% and 98.80%, respectively and thus increased seed yield up to 56.47% over control. J. Environ. Sci. & Natural Resources, 11(1-2): 191-197 2018